Human leukocyte antigen associations with protection against tuberculosis infection and disease in human immunodeficiency virus-1 infected individuals, despite household tuberculosis exposure and immune suppression. (January 2021) - Seedat, Faheem; James, Ian; Loubser, Shayne; Waja, Ziyaad; Mallal, Simon A.; Hoffmann, Christopher; Tiemessen, Caroline T.; Chaisson, Richard E.; Martinson, Neil A.
Abstract: Background: To determine the association of human leukocyte antigen (HLA) alleles as correlates of risk for and protection against tuberculin skin test (TST) positivity and active TB disease amongst HIV-infected adults. Methods: Genomic DNA was extracted from 754 HIV-infected adults whole-blood. HLA-A, -B, -C and -DRB1 loci were genotyped by next generation sequencing methods. HLA alleles were analysed by the presence/absence of TST immune conversion and active TB disease and further stratified by exposure to a household TB contact, CD4 + T-cell count and, for active TB disease, TST-positivity. Results: HLA-A*29:11 and - B*45:01/07 were associated with TST-positivity, while HLA-A*24:02, -A*29:02 and -B*15:16 with TST-negativity. In participants with a household TB contact, HLA - A*66:01, -A*68:02 and -B*49:01 were associated with TST-negativity . For TB disease, HLA-B*41:01, -C*06:02, -DRB1*04:01 and - DRB1*15:01 were associated with susceptibility, while HLA-B*07:02 and -DRB1*11:01 were protective, even for CD4 + T-cell count <350 cells/mm 3 . For initial TST-positivity and subsequent TB disease, HLA-A*01:01 and -DRB1*11:01 conveyed protection including for those with CD4 + T-cell count <350 cells/mm 3 . Conclusion: Several HLA alleles are noted as correlates of TB infection, risk and natural protection in HIV-infected individuals. HLA associations may enable risk stratification of those with HIV infection. Protective alleles may assist in future TB vaccine development. Highlights: HLA allelic variation affects susceptibility to and protection against TB infection. Data describing HLA associations with TB in HIV-positive individuals is limited. Some HLA alleles are associated with protection against TB co-infection in HIV. Knowledge of protective HLA alleles may assist with future vaccine development.